ADME of Bromo-DragonFLY as an example of a new psychoactive substance (NPS) – application of in Silico methods for prediction: absorption, distribution, metabolism and excretion - Maciej Noga; Kamil Jurowski (Scientific Reports)
Abstract Bromo-DragonFLY, a new psychoactive substance (NPS) within the phenethylamine class, is noted for its exceptional potency and prolonged psychoactive effects. Despite its severe toxic reactions and fatalities, research on its human metabolic fate remains limited. This study predicts the absorption, distribution, metabolism, and excretion (ADME) of Bromo-DragonFLY using in silico methods. Results indicate high gastrointestinal absorption and potential blood-brain barrier penetration, enhancing its central nervous system effects. The compound shows significant plasma protein binding and involves multiple cytochrome P450 isoenzymes in its metabolism, with variability in phase I and II reactions. Predicted metabolites form through epoxidation, quinone formation, UGT conjugation, and N-dealkylation, exhibiting reactivity with proteins, DNA, and glutathione, contributing to its toxicological profile. Excretion is predicted mainly via renal pathways. These insights are crucial for understanding the toxicological risks of Bromo-DragonFLY, exemplifying the challenges posed by NPS.